2012
DOI: 10.1155/2012/140147
|View full text |Cite
|
Sign up to set email alerts
|

The Nude Mouse as Model for Liver Deficiency Study and Treatment and Xenotransplantation

Abstract: We aimed at reviewing the various uses of Nude mouse for the development of liver deficiency models and evaluation of efficacy of hepatic cell xenotransplantation. The first part records the large range of liver deficiency models that can be developed in Nude mice: surgical partial hepatectomy, acute toxic liver deficiency, chronic cirrhosis, and transgenic liver injury. The second part tackles the outcome of rat hepatocyte as well as human cell transplantation, both mature hepatocyte and hepatic progenitor, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
1
3
0
Order By: Relevance
“…For NOD.SCID mice, we obtained a 100% survival rate when the hepatectomy was restricted up to the resection of the left liver lobe, which is close to 30% of the total liver mass. In line with the observations on nude mice 27 , we observed that any further increase in the percentage of hepatectomy in NOD.SCID mouse leads to a dramatic lowering of the survival rate. Moreover, proliferation of hepatocytes in the remaining liver lobes post 1 day of 30% partial hepatectomy confirmed the utility of this procedure in transplantation and engraftment studies.…”
Section: Discussionsupporting
confidence: 89%
“…For NOD.SCID mice, we obtained a 100% survival rate when the hepatectomy was restricted up to the resection of the left liver lobe, which is close to 30% of the total liver mass. In line with the observations on nude mice 27 , we observed that any further increase in the percentage of hepatectomy in NOD.SCID mouse leads to a dramatic lowering of the survival rate. Moreover, proliferation of hepatocytes in the remaining liver lobes post 1 day of 30% partial hepatectomy confirmed the utility of this procedure in transplantation and engraftment studies.…”
Section: Discussionsupporting
confidence: 89%
“…Since the homozygous disruption of the Mdr2 gene in mice causes an insufficient excretion of phospholipids into the bile, the histological features found in Mdr2−/− mice are similar to primary sclerosing cholangitis and biliary fibrosis [19]. Chronic chemical hepatic injury and advanced liver fibrosis in BALB/c nude mice was induced by CCl 4 intraperitoneally injection at a dose of 1 mL/kg, dissolved in olive oil (1:4), twice a week for 5 weeks [20]. Hepatocellular carcinoma was induced by intrahepatic implantation of 5 × 10 6 Hepa1-6 cells into BALB/c nude mice via open surgical technique and imaging procedures were performed after 14 days [21].…”
Section: Chemicals and Cellsmentioning
confidence: 99%
“…Liver ischemia-reperfusion injury involved partial ischemia induced by clamping the portal vein and hepatic artery supplying the median and left lobes for 45 min, followed by clamp removal to allow reperfusion in the liver for periods of 6 h and 24 h before imaging. Advanced liver fibrosis was induced by carbon tetrachloride (CCl 4 ) injected twice a week for 5 weeks [37]. Primary sclerosing cholangitis and biliary fibrosis were modelled by 20-week-old Mdr2-/-mice because they show histological features similar to humans [38].…”
Section: Liver Disease Modelsmentioning
confidence: 99%